Preterm Delivery: Predictive Value of Salivary Estriol, and Alpha Feto Protien - Aseel Abdulameer Mohammed; Afrah Makki Mohammed; Shaymaa Raouf Tawfeeq (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Preterm labor is defined by the presence of painful uterine contractions that lead to progressivechanges in the cervix that allow descent and delivery of the newborn before the 37th week of gestation.Objective: To assess the predictive value of salivary estriol and Alpha feto protein in preterm delivery.Patients and Method: A prospective study were carried out in our hospital during the period from 1/1/2020to the 30/8/2020 among the patients who attended for consultation, 120 patients with gestational age between16 and 18 weeks were selected and divided into two groups. Results: The serum level of Alpha-feto proteinwas (338. 15 ± 182.55 in case group vs. 239. 68 ± 112. 51 in control group) with significant association(p=0.01). In spite of the decrease of the estriol level in preterm group we found no significant differenceswere found between both groups regarding the estriol level (P>0.05)Conclusion: The increase in free estriol in saliva in this study was not significantly associated with pretermdelivery in asymptomatic patients at risk, and there is a significantly increase in AFP concentration inpreterm pregnant patients.